Comparative role of non-stress test and colour doppler in high risk pregnancy predicted by placental histopathology and foetal outcome - Paliwal, Shruti; Shaheen, Rizwana; Paliwal, Shweta; Parakh, Poonam; Yadav, Kanchan; Chaudhary, Goury; Jalandhara, Jitendra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Assessment of the foetal wellbeing is done by various biophysical methods. Non stress test (NST) is the most commonly used test for antepartum evaluation of foetal status. It involves the use of doppler-detected foetal heart rate acceleration coincident with foetal movement perceived by mother. Duplex sonography and its off-shoot, colour duplex sonography, are relatively newer methods that combine the pulsed echo technique of sectional image formation with the doppler evaluation of blood flow. Methods: The comparative study was carried out on 200 booked term pregnant patients in the department of Obstetrics and Gynaecology, Dr. S. N. Medical College, Jodhpur Rajasthan, India. All patients were subjected to non-stress test and colour doppler and were evaluated for placental histopathology and foetal outcome in terms of low APGAR score, number of NICU admissions and perinatal mortality. Results: In our study it was found that in high-risk group 25% had non-reassuring NST and 19% had doppler findings suggestive of foetal hypoxia. In the control group 13% had non-reassuring NST and 4% had doppler findings suggestive of foetal hypoxia. It was seen that when either NST was non-reassuring or colour doppler suggested foetal hypoxia or both, these patients required admissions antenatally, had meconium stained liquor suggestive of foetal distress, had operative delivery for foetal distress, had low APGAR score, required NICU admission, and higher perinatal mortality. Conclusions: Doppler and NST are effective in predicting a normal healthy foetus. Doppler depicts chronic hypoxic changes while NST can detect acute events in presence or absence of chronic hypoxia.